2008
DOI: 10.1159/000134917
|View full text |Cite
|
Sign up to set email alerts
|

HPV Typing in Women with Cervical Precancerous and Cancerous Lesions in Northwestern Iran

Abstract: Background/Aims: The role of human papillomavirus (HPV) in the etiology of cervical cancer is now well established. This investigation was designed to study the prevalence of the four most common high-risk HPVs in the archival tissues with precancerous and cancerous lesions from patients from northwestern Iran. Methods: 133 formalin-fixed paraffin-embedded tissue specimens were tested for HPV DNA by using GP5+/6+-based general PCR and two type-specific PCRs. Results: In total, 84 (64%) out of 131 amplifiable s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 51 publications
3
17
0
Order By: Relevance
“…HPV16 and 18 accounted for over 80% of ICC in Iran, confirming the high prevalence of HPV16 observed in ICC from Iran9–12 and Western Asia in general13 compared to other world regions. This data would suggest that the predominance of HPV16 and 18 over other high‐risk types might be even greater in settings of low HPV exposure.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…HPV16 and 18 accounted for over 80% of ICC in Iran, confirming the high prevalence of HPV16 observed in ICC from Iran9–12 and Western Asia in general13 compared to other world regions. This data would suggest that the predominance of HPV16 and 18 over other high‐risk types might be even greater in settings of low HPV exposure.…”
Section: Discussionsupporting
confidence: 63%
“…6,7 HPV prevalence was not statistically higher in younger women, confirming the flat agespecific curve seen in other low-resource countries in Asia and Africa, 8 albeit at lower HPV prevalence. HPV16 and 18 accounted for over 80% of ICC in Iran, confirming the high prevalence of HPV16 observed in ICC from Iran [9][10][11][12] and Western Asia in general 13 compared to other world regions. This data would suggest that the predominance of HPV16 and 18 over other high-risk types might be even greater in settings of low HPV exposure.…”
Section: Discussionsupporting
confidence: 56%
“…Among HPV-positive dysplasia and metaplasia cases, 55.6% had HPV16 and 18 (Hamkar et al, 2002). In another series, 64% of lesion samples proved positive, mostly for 16, 31 or 18 (Esmaeili et al, 2008). High rates of infection with HPV genotypes have also been reported in sexually active Iranian women, again with HPV16 and 18 (Ghaffari et al, 2006).…”
Section: Discussionmentioning
confidence: 89%
“…These data suggest the distribution of HPV16 and 18 in cervical lesions might be different from that in other regions of Pakistan, as in South Karachi the prevalence of HPV16 infection has been reported to be associated with 75%–93% of carcinomas whereas HPV18 infection is associated with 4%–6.6% [11,12]. Studies in other countries of a similar cultural background have also reported a high prevalence of HPV16 infection in cervical lesions collected from Iran (76% [22], 75% [23], 67.6% [24]) and Saudi Arabia (65.2% [25]) with a corresponding low HPV18 prevalence. However, another study conducted in Iran showed that HPV18 was more commonly detected in cervical lesions than HPV16 (41% HPV18 positive and 29.5% HPV16 positive) [26].…”
Section: Resultsmentioning
confidence: 99%
“…However, a study in Thailand has indicated a high incidence of HPV16 (83.2%) and HPV18 (59.3%) in cervical cancer and lesions taken from women in four regions of Thailand and a high incidence of multiple infections, most notably 16/18 in 27.8% of samples and 16/18/11 in 20.4% of samples [28]. Co-infection with multiple HPV types was also noted in 15.3% of cervical specimens collected in Northwestern Iran but the majority of these cases of co-infection were HPV types 16 and 31 [24]. …”
Section: Resultsmentioning
confidence: 99%